1998
DOI: 10.1002/(sici)1098-1136(199803)22:3<221::aid-glia2>3.3.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine synthetase (GS) activity and spatial and temporal patterns of GS expression in the developing chick retina: Relationship with synaptogenesis in the outer plexiform layer

Abstract: The profile of glutamine synthetase (GS) activity in the neural retina of chicken embryos and adults was studied alongside the in vivo spatio-temporal patterns of generation and morphogenesis of Müller cell and of retinal synaptogenesis. The rise of GS activity during development is not related to Müller cell differentiation but to synaptogenesis in the outer plexiform layer (opl). GS expression was investigated by immunoreaction with GS-specific antiserum. Three spatial gradients of decreasing labeling were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 0 publications
4
15
0
1
Order By: Relevance
“…In our experiments Glu-induced increases in GS activity occurred only in mixed neuronal-glial cultures (young or mature), correlating with previous studies indicating that neuron-glial cell contacts are required in the regulation of GS (Vardimon et al, 1988;Mearow et al, 1990). Moreover, Germer et al (1997) demonstrated that GS expression in mammalian Mü ller cells was dependent on environmental factors, and recently Prada et al (1998) suggested that GS expression in the chick retina is mediated by Mü ller cell-neuron interactions. Immunolabelling of purified glia using anti-GS antibody did not change after Glu exposure, indicating that EAA by themselves do not upregulate glial GS expression.…”
Section: Modulation Of Gs Expressionsupporting
confidence: 91%
“…In our experiments Glu-induced increases in GS activity occurred only in mixed neuronal-glial cultures (young or mature), correlating with previous studies indicating that neuron-glial cell contacts are required in the regulation of GS (Vardimon et al, 1988;Mearow et al, 1990). Moreover, Germer et al (1997) demonstrated that GS expression in mammalian Mü ller cells was dependent on environmental factors, and recently Prada et al (1998) suggested that GS expression in the chick retina is mediated by Mü ller cell-neuron interactions. Immunolabelling of purified glia using anti-GS antibody did not change after Glu exposure, indicating that EAA by themselves do not upregulate glial GS expression.…”
Section: Modulation Of Gs Expressionsupporting
confidence: 91%
“…Glutamine synthetase (GS) is a characteristic marker of glial Müller cells in avian retina (Prada et al 1998).…”
Section: Pecteneal Hyalocytes Express Markers Of Neuroglial Cellsmentioning
confidence: 99%
“…An array of different endogenously released neurotransmitters (ACh, dopamine/L-Dopa, glycine, GABA, glutamate) were reported to trigger and to modulate calcium waves, which occur in the chick retina from E7/8 on. GABAergic, glutamatergic, muscarinic, nicotinic acetylcholine, and AMPA receptors are present shortly before or during the period when spontaneous activity occurs, spread across the retinal layers, and from central to peripheral retina (Catsicas et al, 1998Hering and Kröger, 1996;Kubrusly et al, 2003;Pearson et al, 2002;Prada et al, 1998;Silveira dos Santos Bredariol and Hamassaki-Britto, 2001;Vailati et al, 2003;Yamashita and Fukuda, 1993).…”
Section: Chemical Synapses Occur In Both Plexiformmentioning
confidence: 99%
“…Presynaptic proteins are present concurrent with the forming IPL and they spread following the spatial course of the maturating retina (Bergmann et al, 1999(Bergmann et al, , 2000Hering and Kröger, 1996). Glutamine synthetase activity suggests the onset of synaptogenesis in the OPL on E9 (Prada et al, 1998). Consequently, one may assume that synaptogenesis starts much earlier than presently acknowledged and that this process begins in the central retina.…”
Section: Introductionmentioning
confidence: 99%